Ragweed - Avi; Floca, Brian (New York Avon Books, 1999)
Ragweed, a young country mouse, leaves his family and travels to the big city, where he finds excitement and danger and sees cats for the first time.
Prequel to: Poppy.
690L
77035
Keywords: Mice -- Fiction; Cats -- Fiction